Induction Lactation in Islamic Law Studies and Indonesian Positive Law - Khusnul Amalia (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2024)
This study aims to examine the legal status of the practice of induced lactation using synthetic hormone injections under Islamic law and Indonesian positive law, as well as its impact on the status of the nursing child and mahram relationships. This is a literature study that analyzes texts from Indonesian positive law, the perspectives of the four Islamic schools of thought, fatwas from the Indonesian Ulama Council on radha'ah , and other supporting articles. The focus is on elucidating legal values and norms, as well as supporting arguments, using a comparative method between Islamic and Indonesian positive law. The library data are analyzed comparatively using a juridical-normative approach to illustrate the legislative scope of both legal systems and highlight aspects that remain contentious. Findings indicate that the practice of induced lactation with synthetic hormone injections is permissible in both Islamic and Indonesian positive law, provided that the substances used are free from haram elements and do not pose health risks to the woman or the child. However, according to the four Islamic schools of thought, the status of the nursing child is still determined by the origin of the milk production, not by the use of synthetic hormones.